Combined Interactions of Plant Homeodomain and Chromodomain Regulate NuA4 Activity at DNA Double-Strand Breaks. Issue 1 (10th November 2015) - Su, Wen-Pin; Hsu, Sen-Huei; Chia, Li-Chiao; Lin, Jui-Yang; Chang, Song-Bin; Jiang, Zong-da; Lin, Yi-Ju; Shih, Min-Yu; Chen, Yi-Cheng; Chang, Mau-Sun; Yang, Wen-Bin; Hung, Jan-Jong; et al.
Abstract: DNA double-strand breaks (DSBs) represent one of the most threatening lesions to the integrity of genomes. In yeast Saccharomyces cerevisiae, NuA4, a histone acetylation complex, is recruited to DSBs, wherein it acetylates histones H2A and H4, presumably relaxing the chromatin and allowing access to repair proteins. Two subunits of NuA4, Yng2 and Eaf3, can interact in vitro with methylated H3K4 and H3K36 via their plant homeodomain (PHD) and chromodomain. However, the roles of the two domains and how they interact in a combinatorial fashion are still poorly characterized. In this study, we generated mutations in the PHD and chromodomain that disrupt their interaction with methylated H3K4 and H3K36. We demonstrate that the combined mutations in both the PHD and chromodomain impair the NuA4 recruitment, reduce H4K12 acetylation at the DSB site, and confer sensitivity to bleomycin that induces DSBs. In addition, the double mutant cells are defective in DSB repair as judged by Southern blot and exhibit prolonged activation of phospho-S129 of H2A. Cells harboring the H3K4R, H3K4R, K36R, or set1 Δ set2 Δ mutant that disrupts H3K4 and H3K36 methylation also show very similar phenotypes to the PHD and chromodomain double mutant. Our results suggest that multivalent interactions between the PHD, chromodomain, and methylated H3K4 and H3K36 act in a combinatorial manner to recruit NuA4 and regulate the NuA4 activity at the DSB site.